PENGEMBANGAN MEDIA DIORAMA PADA MATERI IPA SIKLUS HIDROLOGI KELAS V SDN KARANGTENGAH 3 KABUPATEN KEDIRI - Dwi Jagat Indrianti; Wahyudi; Bagus Amirul Mukmin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research and development is to determine the validity, practicality and effectiveness of class V hydrological cycle diorama media at SDN Karangtengah 3. This research method uses the R & D (Research and Development) method with the ADDIE model, which consists of 5 stages, including (1) Analysis, (2) Design (planning), (3) Development (development), (4) Implementation ( implementation), (5) Evaluation (evaluation). The results of this research show that. (1) The validation results obtained from material experts received a percentage of 86% and media experts received a percentage of 84%, so the results from material validation and hydrological cycle diorama media are included in the very valid criteria. (2) The results of the teacher response questionnaire received a percentage of 92% and the results of the student response questionnaire received a percentage of 100%, so these results can be concluded that the hydrological cycle diorama media is very practical. (3) The results of the evaluation or posttest questions in the limited trial got an average score of 81 with a classical completeness of 87.5% and in the extensive trial got an average score of 86 with a classical completeness of 100%, so it can be stated that the hydrological cycle diorama media very effective. Keywords: diorama, hydrological cycle science, learning media